THE PHENOMENA OF MOTORCYCLE-TAXI OR OJEK AS PUBLIC TRANSPORTATION IN JAKARTA AND ITS LEGITIMACY ACCORDING TO TRAFFIC AND TRANSPORTATION LAW - Ignatius Roberto (President University, 2016)
Jakarta mostly known for its problem with traffic jam and also their public transportation. Amongst this issue, ojek emerge and established themselves as an alternative public transportation that much faster and accessible compared to other public transportation, especially after the emergence of application-based ojek. Traffic and road transportation have important role in supporting development and as a part to advancing national welfare of the people. The law that provides regulation of transportation itself already exist in Law No. 22 of 2009 of Traffic and Transportation and further regulation in Government Regulation Number 74 of 2014 of Road Transportation, Regional Regulation of Province of Jakarta Number 5 of 2014 of Transportation and Minister of Transportation’s Decision Number KM. 35 of 2003 of Implementation of People’s Transportation in the Road with Public Transportation. A good proper public transportation provides six point that safety, security, comfortness, affordability, equality, and regularity. While, during these days public transportation mostly are unable to fulfill those six point. These situation makes ojek came up with solution as an option for people to through the traffic in Jakarta. But, yet ojek in Jakarta and in Indonesia itself still not regulated and actually becomes illegal public transportation. And the absence of law itself leads to some problem such as price, safety issues, and no customer service provided. In doing this research Author was using socio-legal study and also sociological approach. Author conducted two researches, one for customer of ojek and one for ojek driver. Author used questionnaire for the customer and interview for the ojek driver. Based on research conducted by Author, the absence of law leads into legal uncertainty in the society for the related parties; no regulation that regulates standard or measurement about ojek’s fare and safety. And according to both customer and ojek driver asked by Author also prefer a regulation to be created than to prohibit ojek itself. In this chaotic Jakarta’s traffic and its public transportation that still under development, ojek provides people with option for people. But a regulation still needs to be created to gives legal certainty for parties; whether to protect customer and ojek drivers.